Determination of metals in Brazilian coconut water using an inductively coupled plasma optical emission spectrometer - Sousa,Rafael A. de (2005)
The metal content of coconut water was investigated in samples from different Brazilian states. Ca, Mg, Mn, Fe, Zn and Cu were determined without a mineralization step using the ICP OES technique. Employing optimized instrumental parameters, RSD usually lower than 2% and good accuracy were obtained. LOD values (mg L-1) were: Ca 0.06, Mg 0.004, Mn 0.02, Fe 0.16, Zn 0.008 and Cu 0.006. The concentration ranges (mg L-1) of the analytes in the samples studied were: Ca (107 - 237), Mg (50 - 88), Mn (1 - 5) and Zn (0.04 - 0.18). Considering the Reference Daily Intakes for Minerals (RDI) it was estimated that the nutritional contribution from the ingestion of 400 mL of the beverage corresponds to approximately 7% of the RDI for Ca and Mg and 58% for Mn.